Spontaneous KRT5 Gene Mutation in Rhesus Macaques (Macaca mulatta): A Novel Nonhuman Primate Model of Epidermolysis Bullosa Simplex. Issue 2 (March 2020) - Johnson, Amanda L.; Peterson, Samuel M.; Terry, Margaret M. L.; Ferguson, Betsy; Colgin, Lois M.; Lewis, Anne D.
Epidermolysis bullosa simplex (EBS) is an inherited skin disorder characterized by increased skin and mucous membrane fragility. Most cases are caused by mutations in keratin 5 ( KRT5 ) and keratin 14 ( KRT14 ). Mutations of these genes result in cytoskeletal disruption of the basal keratinocytes. Gross and histopathologic findings of 2 clinically affected homozygous rhesus macaques with an insertion variant mutation in KRT5 are described and compared with 6 deceased phenotypically normal animals that were heterozygous for the KRT5 insertion variant. Animals that were homozygous for the KRT5 insertion variant were stillborn and had widespread loss of the epidermis. Microscopic examination confirmed severe ulceration and basal cell vacuolation with basilar vesicle formation in the remaining intact epidermis. Immunohistochemistry for cytokeratin 5 demonstrated lack of epidermal immunoreactivity in homozygotes. DNA sequencing identified a 34–base pair insertion variant in exon 5 of the KRT5 gene. To our knowledge, this is the first report of epidermolysis bullosa in rhesus macaques.